THE IMPLEMENTATION OF PROJECT-BASED LEARNING ON STUDENTS’ CREATIVITY AND LEARNING MOTIVATION AT SMK PRATAMA WIDYA MANDALA BADUNG: Penerapan Model Pembelajaran Project Based Learning Terhadap Kreativitas Dan Motivasi Belajar Siswa di SMK Pratama Widya Mandala Badung - Ni Made Erpia Ordani Astuti; I Wayan Suryanto; Putu Andyka Putra Gotama (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Vocational education is required to produce graduates who are creative and possess high learning motivation in order to be well prepared for the world of work. However, low levels of creativity and learning motivation among students remain a persistent problem in many vocational high schools. This study aims to analyze the effect of implementing the Project Based Learning (PjBL) model on the creativity and learning motivation of Grade X students at SMK Pratama Widya Mandala Badung. The research employed a quantitative approach using a quasi-experimental design with pre-test and post-test procedures. The research sample consisted of 40 students selected through purposive sampling. Creativity was measured based on the Torrance Creative Thinking indicators, while learning motivation was assessed using the framework of the Motivated Strategies for Learning Questionnaire (MSLQ). Data were analyzed using the Paired Sample t-Test and effect size analysis. The results indicate that the implementation of PjBL has a significant effect on improving students’ creativity and learning motivation (p < 0,05), with effect size values ranging from moderate to large. These findings demonstrate that PjBL is an effective instructional model for enhancing the quality of vocational learning. This study recommends the sustained implementation of PjBL and encourages further research in broader educational contexts and at different educational levels.